Feeding Rumensin to yearling heifers on late-summer grass - Jensen, M.; Held, R.; Smith, E.F.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Rumensin was self-fed in a loose salt mixture to yearling heifers on late-summer bluestem pasture (August to November). They ate 0.036 lbs. of salt mixture (124 mg of Rumensin) daily, but performance did not improve.
Keywords: Beef; Rumensin; Heifers; Bluestem pasture